2014
DOI: 10.1007/s00253-014-5573-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ribosome recycling factor is responsible for improvement of nucleotide antibiotic-toyocamycin in Streptomyces diastatochromogenes 1628

Abstract: Ribosome recycling factor (RRF), a product of the frr gene, is responsible for the dissociation of ribosomes from messenger RNA after the termination of translation. In order to overexpress frr gene in the toyocamycin (TM) producer Streptomyces diastatochromogenes 1628, we cloned and placed the gene under the control of the constitutive promoter PermE(*). The resulting plasmid pIB139-frr was integrated into the chromosome of S. diastatochromogenes 1628 by conducting intergeneric conjugation. The strain S. dias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…The integration of plasmid pIB139‐ toy G into the chromosome of S. diastatochromogenes 1628 was verified by PCR. As determined by qPCR, copy number of toy G in S. diastatochromogenes 1628‐TOYG was two times as much as the copy number in the wild‐type strain (data no shown), indicating that the plasmid containing toyG had been integrated into the unique chromosomal attachment site att B, this was consistent with that of prior work . The specific activity of TOYG of S. diastatochromogenes 1628‐TOYG and wild‐type strain was 3.4 U/mg protein and 2.3 U/mg protein, respectively (Table ).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The integration of plasmid pIB139‐ toy G into the chromosome of S. diastatochromogenes 1628 was verified by PCR. As determined by qPCR, copy number of toy G in S. diastatochromogenes 1628‐TOYG was two times as much as the copy number in the wild‐type strain (data no shown), indicating that the plasmid containing toyG had been integrated into the unique chromosomal attachment site att B, this was consistent with that of prior work . The specific activity of TOYG of S. diastatochromogenes 1628‐TOYG and wild‐type strain was 3.4 U/mg protein and 2.3 U/mg protein, respectively (Table ).…”
Section: Resultssupporting
confidence: 88%
“…E. coli/Streptomyces shuttle vector pIB139 was gifted by Prof. Deng Z. X. Plasmids pIB139‐ vgb and pIB139‐ frr were previously constructed by our laboratory . Plasmid pIB139‐ toy G harboring toy G was constructed as the following: The toy G gene was amplified from genome DNA of S. diastatochromogenes 1628 using primers P1 and P2 (Table ), digested with Nde I and Not I, and ligated into Nde I/ Not I site of plasmid pIB139 (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result confirmed that NsdA sr is not only a homologue of NsdA sc but also has similar effects. Subsequently, by heterologous expression of nsdA sr , similar negative effects on morphological differentiation and antibiotic production were observed in S. diastatochromogenes 1628, which is considered a significant industrial producer of the nucleoside antibiotic, TM [35,36].…”
Section: Discussionmentioning
confidence: 81%